INCIDENCE OF PRE-AND POST-HARVEST DISEASES OF SOME CROP PLANTS IN LAFIA, NASARAWA STATE, NIGERIA: THE FARMERS’ FEEDBACK APPROACH (FUDMA JOURNAL OF SCIENCES, 2020)
On a global scale, plant diseases occurring on the field and after harvest have caused significant reductions in crop yield and food availability. This research was aimed at evaluating the incidence of pre- and post-harvest crop damage by pests and diseases of commonly grown crop plants in Lafia, Nasarawa State, Nigeria. Survey of disease incidence was carried out using the farmers’ feedback approach via administration of semi-structured questionnaires. The report of 50 food and cash crop farmers in five different locations (Lafia North, Lafia South, Lafia West, Lafia East and Lafia Central) of the study area revealed that on-field tissue damage by insect pests had the highest mean occurrence (45.83%), and differed significantly from wilting (13.17%), leaf discolouration (11.50%), stunted growth (1.67%) and leaf necrosis (1.00%) (P≤0.05). The months of October and August were reported as having the highest incidences of pre-harvest (17.00%) and post-harvest (20.00%) diseases respectively. Differences in the incidences of crop diseases on the field and in storage were significant (P≤0.05). Findings of the study revealed that insect damage of crop tissues was the most reported cause of pre- and post-harvest crop losses, and the incidence of crop diseases were highest in the rainy reasons. Sensitization of cash crop farmers on the need for proper crop disease diagnosis and the application of appropriate control measures will help preserve yield and forestall the consequent abuse of chemical pesticides in the study area.
Keywords: Crop losses, Disease symptoms, Lafia, Post-harvest, Pre-harvest